Varieties of capitalism in light of the euro crisis. Issue 1 (2nd January 2018) - Hall, Peter A.
ABSTRACT: This article examines the implications of the euro crisis for theories of political economy associated with 'varieties of capitalism', considering how those theories help explain the origins of the crisis and how developments during it mandate revisions in such theories. Efforts to understand the crisis have extended these theories in four directions. They have inspired an emerging literature on growth models that integrates the demand side of the economy into theories once oriented to its supply side. They have led to more intensive investigation of the political economies of East Central Europe and Southern Europe. The crisis has drawn attention to the international dimensions of varieties of capitalism and to problems of adjustment, injecting an element of dynamism into varieties of capitalism analyses and underlining that adjustment is a political as well as an economic problem.